2011
DOI: 10.1016/j.biomaterials.2011.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of osteogenic differentiation of human mesenchymal stem cells on titanium surfaces by a Wnt-integrin feedback loop

Abstract: Peri-implant bone formation depends on the ability of mesenchymal cells to colonize the implant surface and differentiate into osteoblasts. Human mesenchymal stem cells (HMSCs) undergo osteoblastic differentiation on microstructured titanium (Ti) surfaces in the absence of exogenous factors, but the mechanisms are unknown. Wnt proteins are associated with an osteoblast phenotype, but how Wnt signaling regulates HMSC differentiation on microstructured Ti surfaces is not known. HMSCs were cultured on tissue cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
120
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 47 publications
11
120
0
Order By: Relevance
“…In the present study, Wnt5a levels increased in response to TNF-a in human differentiating osteoblasts. We also report that Wnt5a stimulated TNAP activity in hu- man osteoblasts [28,40,41]. We hypothesize that Wnt5a stimulates TNAP and mineralization through inhibition of PPAR activity in osteoblasts [25,30].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the present study, Wnt5a levels increased in response to TNF-a in human differentiating osteoblasts. We also report that Wnt5a stimulated TNAP activity in hu- man osteoblasts [28,40,41]. We hypothesize that Wnt5a stimulates TNAP and mineralization through inhibition of PPAR activity in osteoblasts [25,30].…”
Section: Discussionsupporting
confidence: 54%
“…Wnt5a, Dkk1 and anti-Dkk1 antibodies were purchased from R&D Systems (Lille, France). We used mouse Wnt5a, which shares 97% homology with human Wnt5a and is biologically active in human cells [28]. Anti-Wnt5a antibodies were from Santa-Cruz (Heidelberg, Germany).…”
Section: Chemicalsmentioning
confidence: 99%
“…Similar observations have been reported in several different TiO 2 dental implant surfaces in in vitro and in vivo rat tibia studies. 11,[35][36][37][38] The proposed mechanism of titanium-associated osteoinduction is thought to be related to hydroxyl groups and calcium ions present in TiO 2 surfaces. These hydroxyl groups may well promote adsorption of calcium-binding extracellular matrix proteins (e.g., alkaline phosphatase) and RGD-specific peptide sequences (e.g., fibronectin, bone sialoprotein).…”
Section: Discussionmentioning
confidence: 99%
“…10 Titania additives may constitute an advantage by increasing surface hydrophobicity and protein adsorption to further enhance cell adhesion, osteogenic induction, and formability in bone biomaterials, including in HAP-GEL. 7,11,12 Consequently, bone regeneration of formable titanium dioxide (TiO 2 )-enriched HAP-GEL scaffolds was compared in this study to HAP-GEL alone.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, nonphosphorylated β-catenin from the destruction complex and FRAT1 translocate into the nucleus to react with TCF/LEF transcription factors and regulate downstream genes, including those involved in bone formation, such as Runx2, Col-1, and OPN is induced. 49 It has been reported that Wnt/β-catenin signaling pathway mediates the biological effects of the microstructured titanium surface, 50,51 while the accumulated data suggests that activation of Wnt signaling is required for regeneration of periodontal tissues such as cementum, periodontal ligament, and alveolar bone. 25,52 Also, it has been reported that temporospatial regulation of Wnt/β-catenin signaling plays an important role in cell differentiation and matrix formation during root and cementum formation.…”
mentioning
confidence: 99%